Method of improving the stability of hop extract and hop flavoured beverages - Wilson, Erica G.; Khatib, Alfi; Zang, Hai-Rong; Verpoorte, Robert (2006)
The present invention relates to a method of improving the stability of hop extracts and hop flavoured beverages as well as to isomerised hop extracts and hop flavoured beverages that exhibit improved stability. More particularly, the present invention relates to hop flavoured beverages containing iso-alpha-acids in a cis/trans ratio of at least 19:1. The invention also concern isomerised hop extract containing iso-alpha-acids in a cis/trans ratio of less than 1:1. The invention encompasses methods of manufacturing the aforementioned beverages and extracts as well as the use of beta-cyclodextrin for separating cis-sio-alpha-acids and trans-iso-alpha-acids, for separating alpha-acids and beta-acids and for enhancing the stability of trans-iso-alpha-acids in hop flavoured beverages.